Breeding Practice Improves the Mycorrhizal Responsiveness of Cotton (Gossypium spp. L.) - Wang, Letian; Wang, Xihe; Maimaitiaili, Baidengsha; Kafle, Arjun; Khan, Khuram Shehzad; Feng, Gu (Frontiers in Plant Science, 2021)
Maximizing the function of indigenous arbuscular mycorrhizal (AM) fungi by choosing specific crop genotypes offers one of the few untapped opportunities to improve the sustainability of agriculture. In this study, we compared the difference in mycorrhizal responsiveness (MR) in plant growth and shoot phosphorus (P) content among cotton (Gossypium spp L.) genotypes from different release dates and then determined the relationships between MR and P uptake-related traits. The experimental design in a greenhouse included 24 genotypes released from 1950 to present in Xinjiang Province, inoculation with or without AM fungi, and P levels (15 and 150 mg P kg-1 added as KH2PO4). Results showed that the modern cotton genotypes exhibited a higher degree of mycorrhizal colonization, hyphal length density and mycorrhizae-induced changes in shoot growth than the old genotypes when inoculated with indigenous AM fungi at both P levels. Moreover, MR was highly correlated with hyphal length density (HLD) at low P levels, and the HLD may provide useful insights for future cotton breeding aimed at delivering crop genotypes that can benefit more from AM fungi.